Synthesis of chiral isoindolinones via asymmetric propargylation/lactamization cascade. Issue 16 (18th April 2018) - Meng, Jiao-Long; Jiao, Tang-Qian; Chen, Ya-Heng; Fu, Rui; Zhang, Shu-Sheng; Zhao, Qian; Feng, Chen-Guo; Lin, Guo-Qiang
Graphical abstract: Highlights: Easy operation, benign reaction conditions and high diastereoselectivity. A practical and efficient method for the synthesis of chiral isoindolinones. Versatile transformations associated with the resulting products. Abstract: A Zn-mediated propargylation/lactamization cascade reaction with chiral 2-formylbenzoate derived N - tert -butanesulfinyl imines was realized, which provided a practical and efficient method for the synthesis of chiral isoindolinones. High diastereoselectivities (up to 97:3 dr) and good reaction yields were observed for most examined cases.